Magnetism in organic diradical ion salts based on nitronyl nitroxide - Sugano, T; Blundell, S; Hayes, W; Day, P (2005)
Magnetism in organic diradical ion salts prepared from the diradicals, pyridine-2,6-diylbis(nitronyl nitroxide) [(2,6-PYBNN)(center dot center dot)] and phenol-2,4-diylbis(nitronyl nitroxide) [(2,4-POBNN)(center dot center dot)], were investigated by using SQUID magnetometers. The diradical cation salt (2,6-PYBNN)Cl--+(-) shows intramolecular ferromagnetic (FM) interaction with the exchange coupling constant J/k = +9.0 K and intermolecular antiferromagnetic (AFM) interaction with the Weiss constant theta = -0.75 K in the low temperature phase below 4.5 K. Although the intramolecular FM interaction is close to that observed in the neutral diradical 2,6-PYBNN.., the intermolecular AFM interaction is significantly reduced from J'/k = -57 K due probably to the increase of intermolecular distances by the incorporation of Cl- ions into the salt. We also present and discuss the magnetic behavior in the diradical cation salt (2,6-PYBNN)center dot center dot+BF4- and the diradical anion salt. (C4H9)(4)N+(2,4-POBNN)(center dot center dot-). (c) 2005 Elsevier Ltd. All rights reserved.